The anti-inflammatory and immunological properties of GLP-1 Receptor Agonists. (August 2022) - Bendotti, Giulia; Montefusco, Laura; Lunati, Maria Elena; Usuelli, Vera; Pastore, Ida; Lazzaroni, Elisa; Assi, Emma; Seelam, Andy Joe; El Essawy, Basset; Jang, Jun; Loretelli, Cristian; D'Addio, Francesca; et al.
Abstract: In the last few years, a great interest has emerged in investigating the pleiotropic effects of Glucagon Like Peptide-1 Receptor Agonists (GLP-1RAs). While GLP-1RAs ability to lower plasma glucose and to induce weight loss has allowed them to be approved for the treatment of diabetes and obesity, consistent evidences from in vitro studies and preclinical models suggested that GLP-1RAs have anti-inflammatory properties and that may modulate the immune-system. Notably, such anti-inflammatory effects target different pathways in different tissues, underling the broad spectrum of GLP-1RAs actions. This review examines some of the currently proposed molecular mechanisms of GLP-1RAs actions and explores their potential benefits in reducing inflammatory responses, which may well suggest a future therapeutic use of GLP-1RAs in new indications. Graphical Abstract: ga1